ZIF-8@ZIF-67–derived ZnCo2O4@nitrogen–doped carbon/carbon nanotubes wrapped by a carbon layer: a stable oxygen reduction catalyst with a competitive strength in acid media. (March 2021) - Li, J.H.; Liu, M.Y.; Li, Y.; Yuan, L.; Zhang, P.; Cai, Z.; Chen, H.; Zou, J.L.
Abstract: Owing to the sluggish reaction kinetics and poor stability of cathodic catalysts for oxygen reduction reaction (ORR) in acidic media, the development of highly active and acid-stable ORR catalysts is of great practical significance. Herein, the prepared ZIF-8@ZIF-67 material, polyvinylpyrrolidone (PVP), and expanded graphite (EG) are used as precursors to prepare the ZnCo2 O4 @nitrogen-doped carbon-carbon nanotubes wrapped by a PVP-derived thin carbon layer anchored on the EG (ZnCo2 O4 @NC-CNTs@PCL/EG) as ORR catalysts. ZnCo2 O4 @NC-CNTs@PCL/EG-10 (weight ratio of ZIF-8@ZIF-67 to EG = 10) has an onset potential of 0.689 V (vs. SCE), which is comparable with that of commercial Pt/C (0.706 V) in the acid electrolyte. After acid pickling, the spinel ZnCo2 O4 as the core is stably and uniformly encapsulated by the NC-CNT skeleton and can fully use the highly active Co 2+ sites to boost the 4e – ORR process with a strong methanol resistance. ZnCo2 O4 @NC-CNTs@PCL/EG-10 shows strong stability and methanol tolerance (a decline of 3.21%) after 3600 s, which are better than those of commercial Pt/C (29 mV and 4.06%). The ORR durability is attributed to the PCL shell that avoids the corrosion of active ZnCo2 O4 and N-species. Therefore, it provides a new idea for designing a spinel-based ZIF derivative as stable ORR catalysts in acid media. Graphical abstract: Image 1 Highlights: MOF-derived (metal-organic framework) ZnCo2 O4 @NC-CNTs@PCL/EG is used as oxygen reduction reaction (ORR) catalysts for the first time. The hollow structure contains more oxygen-containing groups to promote the ORR process. Coupling effect between ZnCo2 O4 and NC-CNTs realizes better CH3 OH tolerance than Pt/C. ZnCo2 O4 @NC-CNTs@PCL/EG gains a comparable ORR activity with Pt/C in acid media. The NC-CNTs@PCL shell can effectively prevent active ZnCo2 O4 from corrosion.